Cactus diversity in the Sierra del Rosario, Durango, Mexico - Estrada Arellano, José Raymundo; Estrada-Castillón, Andres Eduardo; Salinas-Rodriguez, María Magdalena; Sánchez Salas, Jaime; Rueda Puente, Edgar Omar; Márquez Hernández, Candido (Ecosistemas y Recursos Agropecuarios, 2018)
The Sierra del Rosario is a calcareous mountainous area located in the northeast region of the state of Durango, where xerophilous vegetation and chaparral predominate. The aim of this study was to determine cactus diversity and distribution in the region. A list of cacti was obtained from 15, 3 km transects covering the vegetation of microphyllous desert shrubland, rosetophyllous desert shrubland and chaparral. A total of 33 species and 13 genera were recorded, with the most representative genera being Coryphantha, Echinocereus and Mammillaria. There are six species in some category of risk according to NOM-059-SEMARNAT-2010, distributed in the genera Coryphantha, Glandulicactus and Peniocereus. No species was found at risk in the IUCN, while Coryphantha sneedii is in the CITES. Species richness estimators indicate that diversity ranges from 34 to 47 taxa. The greatest diversity is between 1 207 and 1 400 masl in the rosetophyllous desert shrubland.